Past and future of Hebel Haus in Japan: Vergangenheit und Zukunft von Hebel Haus in Japan. Issue 5 (30th August 2018) - Kuroki, Kouji
Abstract: It is 50 years since the AAC (Hebel) technology has been introduced in Japan. During this half century Hebel Haus™ have sold homes using the Hebel AAC in floors, walls, and ceilings. The total number of unit homes sold has now exceeded 250 000, and Hebel Haus homes are constructed in Japan at a rate of about 8 000 units every year. Japan is a country that frequently suffers from natural disasters. To protect customerś lives and properties Hebel Haus has developed a construction method that combines steel‐framed structure with AAC (Hebel) materials. With an integrated system from construction to sales and after‐sale services, renovation, and the second‐hand housing distribution, Hebel Haus has achieved the status of the top urban housing brand in Japan. Here we are going to present an outline of Hebel Haus history, marketing strategy, technologies, designs, and lifestyle proposals in Japan.